Mix design of self-levelling mortar prepared by curshed sand with high flowability and early strengthening. (10th May 2021) - Wu, Miaomiao; Zhao, Qinglin; Shen, Weiguo; Zhao, Jinpeng; Xu, Gelong; Zhao, Deqiang; Xiong, Xing
Highlights: Self-leveling mortar were prepared by crushed sand with large amounts of mineral admixtures and ultrafine cement. V p / V a is an effective mix parameter to optimize the flow properties of mortar. MAPT are related to fluidity and strength with a linear-type equation and quadratic polynomial-type equation respectively. Combination of silica fume and sodium sulfate could work well as hardening accelerator of self-leveling mortar. Abstract: High flowability and early strengthening properties of self-levelling mortar (SLM) could greatly boost construction efficiency and save lots of labor force and materials costs. In this paper, absolute volume method was applied to design the mix proportions of SLM prepared by curshed sand. Further, the relationships between the flowability, strength of mortar and the calculated coating paste thickness MAPT under several paste to aggregate volume fractions ( V p / V a ) were analyzed. Subsequently, ultrafine cement, silica fume and sodium sulfate were added to improve the early-age strength of SLM, and their effects on the flowability and rheological properties were also discussed. Finally, the XRD, TG-DTG analysis and SEM images were applied to study the microstructure of hardened matrix. Results showed that a linear equation could be employed to express the relationship between fluidity and the MAPT and a quadratic polynomial relationship for strength. Rheological parameters were increased by the ultrafine cement and silica fume, while sodium sulfate could enhance the rheological properties. It was found that combination admixture of silica fume and sodium sulfate could improve the mechanical strength greatly. And more C-S-H gels and higher chemical combined water (CCW) content were generated in the sample modified by the combination admixture.